P160 Pan-enteric mucosal inflammation in CD patients treated with vedolizumab – interim results of a prospective observational study using a panenteric capsule (PiilCam CD). (21st January 2022) - Kopylov, U; Lipkin, M; Ungar, B; Haj, O; Shachar, E; Lahat, A; Ben-Horin, S; Eliakim, R
Abstract: Background: Mucosal healing is associated with improved short- and long-term outcomes in Crohn's disease (CD). However, the likelihood of reaching mucosal healing differs between segments of the mucosal tract. The prevalence of panenteric mucosal healing is scarcely described. Capsule endoscopy is the prime modality for evaluation of the entire small bowel. Recently, a combined pan-enteric capsule (PillCam Crohn's capsule (PCCD) that enables evaluation of mucosal inflammation in the entire digestive tract in a single procedure, has been developed. The main aim of our study was to evaluate the rate of panenteric mucosal healing in Crohn's disease patients treated with vedolizumab (VDZ) after 52 weeks of therapy. The current interim report focuses on the rates of mucosal improvement after 14 weeks of VDZ treatment. Methods: This was a prospective open- label observational study. Patients starting vedolizumab (VDZ) for Crohn's disease underwent a patency capsule (PC) and if it was excreted within 30 hours, enrolled in the study. The patients were evaluated with PCCD at week 0, 14 and 52 of VDZ treatment. Mucosal inflammation was quantified using the Lewis score (LS) and the panenteric Pillcam score (PS). In addition, fecal calprotectin (FC) and CRP levels were measured at each visit. Patients without active mucosal inflammation on week 0 PCCD were excluded from further participation Results: We enrolled 30 patients; 5/30 failed PC and were dropped out of the study.Twenty five patients underwent PCCD at week 0 and 19/25 (78%)% -at week14 (six patients were dropped out for either absence of active mucosal inflammation at week 0 (1 patient), treatment discontinuation before week 14 (2 patients) endoscopic activity – 1, withdrawal of consent (1 patient) or loss to follow-up (1 patient)). After 14 weeks of VDZ treatment, there was a significant improvement in LS (median of 900 (interquartile ration (IQR)- 1143)), vs 450 (IQR-750), p=0.013), ES (15 (IQR-18) vs 10 (IQR-11), p=0.012) and FC (996 (IQR-455) vs 742 (IQR -740), p=0.012), while CRP levels were not significantly different. Conclusion: VDZ induces significant improvement in mucosal inflammation evaluated by panenteric capsule endoscopy, in addition to a significant improvement in FC levels, after 14 weeks of therapy *The study was supported by IIR grant from Takeda and Medtronic